Mnestic and intellectual activity of elementary schoolchildren with history of intranatal asphyxia - Y. V. Trusov; V. A. Kramarskiy (Acta Biomedica Scientifica, 2017)
Purpose: to study intellectual activity and memory of elementary schoolchildren who endured intranatal hypoxia and to define primary defect and secondary disturbances of their brain activity. Materials and methods: the neuropsychological research of memory and intelligence in 32 children aged 7-8 years with the history of intranatal hypoxia is conducted (group A). As an including criterion we considered Apgar scale assessment less than 7 points on the first and the fifth minute of life. The control group (group B) included 32 children with a perinatal lesion of the central nervous system whose Apgar scale assessment on the first and the fifth minute of life made 7 and more points. During our research we used methods of observation, experiment, and conversation. Results. In children who endured intranatal hypoxia the following pathological states dominated against the background of asthenia: retarded development of static functions, postural disorder, a cardiopathy, enuresis, accident and chaotic character of visual active thinking, inactivity of mental processes, mental deficiency, disturbed relations between mental activity programing and control of its execution, defective short term and verbal memory. Conclusion: primary defect in children who endured intranatal hypoxia is connected with organic lesion of diencephalic brain structures, with secondary depression of frontal lobes integrative functions and, as a result, with the inadequate organization of visceral and behavioural functional systems. In the neuropsychological syndrome structure increases the importance of diencephalic disturbances along with depression of orientational and exploratory activity, motivation for task performance and control function of attention and speech over the process aspect of activity. Disturbances of voluntary regulation consist in difficulties of forming and realization of programs, disorders in control over ongoing and ultimate results.